Four tsunami indicators needed in the Tanis site, Hell Creek Formation, North Dakota - Monge-Nájera, Julián (2022)
It has been proposed that (1) the Tanis site, Hell Creek Formation of North Dakota, has the fossil remains of a tsunami and that (2) this tsunami was caused by the Chicxulub asteroid impact and the extinction of non-avian dinosaurs. If this interpretation is correct, Tanis should present the typical characteristics of tsunami sites. Here I list the characteristics that Tanis should have if it is a tsunami site.